A Non-Additive Measure of Uncertainty - Shackle, G. L. S. (Review of Economic Studies, 1949)
Journal Article A Non-Additive Measure of Uncertainty Get access G. L. S. Shackle G. L. S. Shackle Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 17, Issue 1, 1949, Pages 70–74, https://doi.org/10.2307/2295790 Published: 01 April 1949